2016
DOI: 10.1016/j.ijcme.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The autocrine role of tryptase in pressure overload-induced mast cell activation, chymase release and cardiac fibrosis

Abstract: Background Cardiac mast cell (MC) proteases, chymase and tryptase, increase proliferation and collagen synthesis in cultured cardiac fibroblasts. However, the question as to why preventing individually the actions of either protease prevents fibrosis when both are released upon MC activation remains unanswered. Since tryptase has the ability to activate MCs in noncardiac tissues via the protease-activated receptor-2 (PAR-2), there is the possibility that its, in vivo, fibrotic role is due to its ability to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…As a pharmacological approach to address the role of tryptase in fibrotic conditions in vivo, Li et al induced cardiac fibrosis in rats by transverse aortic constriction and treated the animals with a selective tryptase inhibitor (nafamostat mesylate). It was found that tryptase inhibition led to ameliorated cardiac fibrosis, in line with a pro‐fibrotic impact of MC tryptase.…”
Section: Targeting Mast Cell Function In Fibrosismentioning
confidence: 99%
See 3 more Smart Citations
“…As a pharmacological approach to address the role of tryptase in fibrotic conditions in vivo, Li et al induced cardiac fibrosis in rats by transverse aortic constriction and treated the animals with a selective tryptase inhibitor (nafamostat mesylate). It was found that tryptase inhibition led to ameliorated cardiac fibrosis, in line with a pro‐fibrotic impact of MC tryptase.…”
Section: Targeting Mast Cell Function In Fibrosismentioning
confidence: 99%
“…In a model of 2,4,6,‐trinitrobenzene sulfonic acid‐induced colitis, Xu et al demonstrated that nedocromil, a cromoglycate derivative, reduced the extent of fibrosis. Nedocromil has also been demonstrated to ameliorate left ventricular fibrosis in spontaneously hypertensive rats and to reduce cardiac fibrosis resulting from transverse aortic constriction . Another MC “stabiliser”, Tranilast, reduced the extent of experimentally induced fibrosis in mice .…”
Section: Targeting Mast Cell Function In Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanisms associated with chymase-mediated cardiac Ang II production may be influenced by multiple factors other than stretch since chronic estrogen treatment attenuates the increases in cardiac Ang II, Ang-(1-7), chymase mRNA, and mast cell number induced in oophorectomized mRen2.Lewis hypertensive rats (150,159). In addition, Li et al (83) reported recently that chymase and tryptase induction of cardiac fibrosis may require the proteaseactivated receptor-2 (PAR-2).…”
Section: H408mentioning
confidence: 99%